Green Talent Management and Innovative Work Behavior: The Mediating Role of Transformational Leadership - Dhakal, Basanta; Biswakarma, Gangaram; Rajkarnikar, Shreeja (Journal of Ecohumanism, 2024)
In today’s rapidly evolving business environment, organizations must foster innovation to maintain competitiveness and sustainability. Employee innovative work behavior plays a crucial role in driving organizational success, yet the factors that influence it remain underexplored. This study examines the impact of green talent management on innovative work behavior, with transformational leadership as a mediating factor. This study adopts a quantitative research approach, using a descriptive and causal research design to collect data from 217 employees in banking sector in Nepal, through a structured questionnaire. The findings indicate that green soft talent management enhances transformational leadership, which in turn fosters innovative work behavior, highlighting the critical role of leadership in promoting innovation. However, green hard talent management does not directly influence transformational leadership or innovative work behavior, and green soft talent management alone does not sufficiently drive innovation without leadership support. Transformational leadership fully mediates the relationship between green soft talent management and innovative work behavior, emphasizing its importance in translating sustainability-driven human resource management practices into employee innovation. This study contributes to social exchange theory, social identity theory, and transformational leadership theory by demonstrating how leadership strengthens the impact of sustainability-focused human resource management on innovation. The findings highlight the importance of transformational leadership in fostering an innovative workforce and ensuring long-term organizational sustainability.